2003
DOI: 10.1136/bmj.327.7408.185
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' emotional reactions to recent death of a patient: cross sectional study of hospital doctors

Abstract: Objectives: To describe doctors' emotional reactions to the recent death of an "average" patient and to explore the effects of level of training on doctors' reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
2
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(213 citation statements)
references
References 20 publications
13
182
2
7
Order By: Relevance
“…Patients were randomly selected from deaths on the medical services at two highly specialized referral medical centers in Boston, Massachusetts, and Pittsburgh, Pennsylvania. 6 Patient deaths were identified by reviewing the charts of all inpatients who died on the internal medicine services during the previous week. An eligible patient case was one in which at least two physicians could be identified who had cared for the patient at the time of death.…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…Patients were randomly selected from deaths on the medical services at two highly specialized referral medical centers in Boston, Massachusetts, and Pittsburgh, Pennsylvania. 6 Patient deaths were identified by reviewing the charts of all inpatients who died on the internal medicine services during the previous week. An eligible patient case was one in which at least two physicians could be identified who had cared for the patient at the time of death.…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…Studies have demonstrated that better communication and more compassionate care reduce patient anxiety and depression, increase a patient's ability to adjust psychologically to the diagnosis, and increase quality of life [18][19][20][21][22][23]. In addition, a close relationship with patients has been found to correlate with physician satisfaction, particularly in care near the end of life [7,24,25]. Thus, a close patient-physician relationship can be beneficial in terms of both patient care and physician satisfaction.…”
Section: How Close Is Too Close?mentioning
confidence: 99%
“…Only 28% of physicians cared for the patients for longer than 7 days, yet 64% of the physicians rated these deaths as moderately or highly powerful, and 45% rated them as moderately or highly disturbing. Longer durations of care and less time as a physician correlated with greater emotional reactions to patients' deaths [7]. A follow-up study evaluated these physicians' most emotionally powerful patient deaths by quantitative survey and qualitative interview.…”
Section: Although I Learned With This Patient and Others That Revealimentioning
confidence: 99%
“…According to Parkes 7 and Redinbaugh et al, 27 the impact of patients' deaths correlates with the following factors: how death occurred, the characteristics of the deceased, professionals' identification with patients and their families, professional performance assessment in providing care for patients, the feeling of responsibility for death, quality of the bond with patients, duration of the bond, individual experience with death and personal history and vulnerabilities.…”
Section: Coping With Death and Dyingmentioning
confidence: 99%
“…The literature discusses measures for facilitating and contributing towards physicians' abilities to process and cope with the emotions and feelings associated with death and dying among their patients. 16,17,[24][25][26][27][28] There are data indicating that workers who do not feel prepared to cope with these situations tend to develop a broad range of reactive feelings, such as: professional loneliness, loss of the sense of mission, cynicism, desperation, frustration and an increased risk of burnout and depression. 16,17 The acknowledgement that medicine is a potentially stressful occupation, has led to increases in prophylactic and/or care measures for physicians and other healthcare workers, over past decades.…”
Section: It Was Clear I Was Conscious Of It: 'I'll Buy That Thing I'mentioning
confidence: 99%